2013
DOI: 10.1039/c3gc41581c
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and origin of char and coke from fast and slow, catalytic and thermal pyrolysis of biomass and relevant model compounds

Abstract: Char and coke from biomass catalytic pyrolysis have different origins. They cannot be lumped as one since they occupy different locations on the catalyst surface and, thus, contribute differently to catalyst deactivation. In this study, catalyst (ZSM-5) deactivation in the perspective of comparison of char and coke from pyrolysis of different biomass types is investigated. Pine sawdust, glucose, and cellulose are used as feedstocks in the pyrolysis experiments. Biomass char and coke samples produced via slow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
104
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 83 publications
(285 reference statements)
1
104
0
1
Order By: Relevance
“…Oddly,h igh heatingr ates (fast pyrolysis) lead to more levoglucosan formation but the levoglucosan quicklyp olymerizesa nd cannotb e recovered. [60,63,[66][67][68][69][70][71] However, physical mixtures of Siral 5, an amorphous silica-alumina, and H-ZSM-5 was shown to have as ynergistic effect on the yield of aromaticsr elative to either catalystalone. Recent isotopic and computational studies suggest that levoglucosan is deoxygenated within the liquid phase and that contraction of the 6-membered glucopyranose ring to the 5-membered glucofuranoser ing is the key process for depolymerization of cellulose.…”
Section: Pyrolysis Of Cellulose and Glucosementioning
confidence: 99%
See 2 more Smart Citations
“…Oddly,h igh heatingr ates (fast pyrolysis) lead to more levoglucosan formation but the levoglucosan quicklyp olymerizesa nd cannotb e recovered. [60,63,[66][67][68][69][70][71] However, physical mixtures of Siral 5, an amorphous silica-alumina, and H-ZSM-5 was shown to have as ynergistic effect on the yield of aromaticsr elative to either catalystalone. Recent isotopic and computational studies suggest that levoglucosan is deoxygenated within the liquid phase and that contraction of the 6-membered glucopyranose ring to the 5-membered glucofuranoser ing is the key process for depolymerization of cellulose.…”
Section: Pyrolysis Of Cellulose and Glucosementioning
confidence: 99%
“…Selectivity to aromatic products or value-added chemicals was determined to be af unction of catalyst/biomass weightr atio, heating rate, pore size, reactorc onfiguration, and reactiontemperature. [67,74,75] It hasb een suggested that char forms as an external layer on the catalyst surfaceand in macropores while coke forms inside micropores. [60,63,[66][67][68][69][70][71] However, physical mixtures of Siral 5, an amorphous silica-alumina, and H-ZSM-5 was shown to have as ynergistic effect on the yield of aromaticsr elative to either catalystalone.…”
Section: Pyrolysis Of Cellulose and Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…Sakata et al carried out studies to understand the effect of position of catalyst for pyrolysis of plastics (polyethylene and polypropylene) and observed significant variations in the product distribution and yields [11]. In case of biomass pyrolysis, experiments on Py-GC/MS to understand the effect of position of catalyst [12][13][14][15] and some preliminary catalytic pyrolysis reports of biomass using H-ZSM-5 [16,17] are available in open literature.…”
Section: Introductionmentioning
confidence: 96%
“…This coke lowers the acidity of the catalyst surface resulting in deactivation (Du et al, 2013). The coke formed on the catalyst can be removed by combustion, and circulating fluidized bed reactors have been employed for continuous catalyst regeneration.…”
Section: Introductionmentioning
confidence: 99%